Oral Administration of Ethanol Extract of Myristica fragrans Elicited Hyperactivity, Anxiety and Reduced Dopamine Level in Rats - SUNDAY Abba; SUNDAY ABRAHAM MUSA; Abel Agbon; SUNDAY OLADELE; IBRAHIM Joseph Momoh; ENYINNA OGBONNA; OLUSEGUN Dare Omotosho (Babcock University Medical Journal)
Objective: Myristica fragrans, a common kitchen spice, is reported to have psychoactive properties, producing hallucinations and fear. The psychoactive action is attributed to the presence of myristicin. This study aimed to assess the effects of ethanol seed extract of Myristica fragrans (ESMF) on anxiety-like behaviour and dopamine levels in rats.